Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the expression [tex]\( -\sqrt{49} - \sqrt{-2} - \sqrt{144} + \sqrt{-72} \)[/tex], let's evaluate each term step by step.
1. Evaluate [tex]\( -\sqrt{49} \)[/tex]:
[tex]\[ \sqrt{49} = 7, \text{ so } -\sqrt{49} = -7. \][/tex]
2. Evaluate [tex]\( \sqrt{-2} \)[/tex]:
This involves the imaginary unit [tex]\( i \)[/tex], where [tex]\( i = \sqrt{-1} \)[/tex].
[tex]\[ \sqrt{-2} = \sqrt{-1} \cdot \sqrt{2} = i\sqrt{2}. \][/tex]
3. Evaluate [tex]\( -\sqrt{144} \)[/tex]:
[tex]\[ \sqrt{144} = 12, \text{ so } -\sqrt{144} = -12. \][/tex]
4. Evaluate [tex]\( \sqrt{-72} \)[/tex]:
Similarly to the previous imaginary number calculation, the imaginary unit [tex]\( i \)[/tex] is involved.
[tex]\[ \sqrt{-72} = \sqrt{-1} \cdot \sqrt{72} = i \cdot \sqrt{72}. \][/tex]
Further simplify [tex]\( \sqrt{72} \)[/tex]:
[tex]\[ \sqrt{72} = \sqrt{36 \cdot 2} = \sqrt{36} \cdot \sqrt{2} = 6\sqrt{2}. \][/tex]
So,
[tex]\[ \sqrt{-72} = 6i\sqrt{2}. \][/tex]
Now, combining all the evaluated parts together in the original expression [tex]\( -\sqrt{49} - \sqrt{-2} - \sqrt{144} + \sqrt{-72} \)[/tex], we have:
[tex]\[ -7 - i\sqrt{2} - 12 + 6i\sqrt{2}. \][/tex]
Combine the real parts and the imaginary parts separately:
- Real parts: [tex]\( -7 - 12 = -19 \)[/tex].
- Imaginary parts: [tex]\( -i\sqrt{2} + 6i\sqrt{2} = 5i\sqrt{2} \)[/tex].
So the final expression in its simplest form is:
[tex]\[ -19 + 5i\sqrt{2}. \][/tex]
This is the final result of the given mathematical expression.
1. Evaluate [tex]\( -\sqrt{49} \)[/tex]:
[tex]\[ \sqrt{49} = 7, \text{ so } -\sqrt{49} = -7. \][/tex]
2. Evaluate [tex]\( \sqrt{-2} \)[/tex]:
This involves the imaginary unit [tex]\( i \)[/tex], where [tex]\( i = \sqrt{-1} \)[/tex].
[tex]\[ \sqrt{-2} = \sqrt{-1} \cdot \sqrt{2} = i\sqrt{2}. \][/tex]
3. Evaluate [tex]\( -\sqrt{144} \)[/tex]:
[tex]\[ \sqrt{144} = 12, \text{ so } -\sqrt{144} = -12. \][/tex]
4. Evaluate [tex]\( \sqrt{-72} \)[/tex]:
Similarly to the previous imaginary number calculation, the imaginary unit [tex]\( i \)[/tex] is involved.
[tex]\[ \sqrt{-72} = \sqrt{-1} \cdot \sqrt{72} = i \cdot \sqrt{72}. \][/tex]
Further simplify [tex]\( \sqrt{72} \)[/tex]:
[tex]\[ \sqrt{72} = \sqrt{36 \cdot 2} = \sqrt{36} \cdot \sqrt{2} = 6\sqrt{2}. \][/tex]
So,
[tex]\[ \sqrt{-72} = 6i\sqrt{2}. \][/tex]
Now, combining all the evaluated parts together in the original expression [tex]\( -\sqrt{49} - \sqrt{-2} - \sqrt{144} + \sqrt{-72} \)[/tex], we have:
[tex]\[ -7 - i\sqrt{2} - 12 + 6i\sqrt{2}. \][/tex]
Combine the real parts and the imaginary parts separately:
- Real parts: [tex]\( -7 - 12 = -19 \)[/tex].
- Imaginary parts: [tex]\( -i\sqrt{2} + 6i\sqrt{2} = 5i\sqrt{2} \)[/tex].
So the final expression in its simplest form is:
[tex]\[ -19 + 5i\sqrt{2}. \][/tex]
This is the final result of the given mathematical expression.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.